The New Coronavirus Infection (COVID-19) and Hearing Function in Adults - Maria Y. Boboshko; Ekaterina S. Garbaruk; Sof'ya M. Vikhnina; Larisa E. Golovanova; Elena A. Ogorodnikova; Anna V. Rabchevskaya; Ekaterina V. Zhilinskaia (MDPI AG, 2022)
In this study, we assessed the impact of COVID-19 on the hearing function in adults. A total of 161 subjects were examined, and the results of a previous audiological examination of 24 patients were reviewed. Pure tone audiometry, impedancemetry, speech audiometry in quiet and noise, the Binaural Fusion Test, the dichotic digits test, and a cognitive status examination were performed. A total of 81% of patients complained about hearing disorders, and 43% noted memory impairment. According to pure tone audiometry, 24% of the subjects had normal hearing, while 76% had some degree of hearing loss. No significant changes in hearing thresholds were found in comparison with audiological examinations performed before COVID-19. Disorder of monosyllabic words' intelligibility in quiet was found in 33% of patients, and in 42% in noise, along with low indicators in the dichotic digits test in 54% of patients. Moreover, 71% of patients had low scores on the MoCA scale that indicated cognitive impairment. Conclusions: The deterioration of speech test scores in patients after COVID-19 can occur due to central auditory processing disorders (CAPD), memory impairment, or changes in cognitive status in general.